2006
DOI: 10.1590/s1516-35982006000200036
|View full text |Cite
|
Sign up to set email alerts
|

Cana-de-açúcar em substituição à silagem de milho em dietas para vacas em lactação: parâmetros digestivos e ruminais

Abstract: RESUMO -O experimento foi realizado com o objetivo de avaliar a substituição da silagem de milho por cana-de-açúcar em dietas para vacas leiteiras. Foram avaliados quatro níveis de substituição (0; 33,3; 66,6 e 100%) de silagem de milho por cana-de-açúcar para o estudo do consumo e da digestibilidade aparente dos nutrientes e a determinação do pH e da concentração de compostos nitrogenados amoniacais (N-NH 3 ) do líquido ruminal e da taxa de passagem ruminal da digesta. Doze vacas da raça Holandesa, puras e me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
4
14
0
16
Order By: Relevance
“…Mendonça et al (2004) evaluated pH and ammonia levels in the rumen fluid of dairy cows fed sugarcane and found that pH declined from 7.2 to 6.8 and N-NH 3 levels increased from 3.8 to 16.6 mg/dL from 0 to 3 h postfeeding. The results found in the present study (Figures 1b and 2b) are closer to those obtained by Magalhães et al (2006), who evaluated the rumen fluid of dairy cows fed sugarcane. For periods 0 (before feeding) and 2, 4 and 6 h post-feeding they found pH values of 6.87, 6.71, 6.60 and 6.79 and N-NH 3 levels of 4.66, 20.25, 12.56 and 7.81 mg/dL, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mendonça et al (2004) evaluated pH and ammonia levels in the rumen fluid of dairy cows fed sugarcane and found that pH declined from 7.2 to 6.8 and N-NH 3 levels increased from 3.8 to 16.6 mg/dL from 0 to 3 h postfeeding. The results found in the present study (Figures 1b and 2b) are closer to those obtained by Magalhães et al (2006), who evaluated the rumen fluid of dairy cows fed sugarcane. For periods 0 (before feeding) and 2, 4 and 6 h post-feeding they found pH values of 6.87, 6.71, 6.60 and 6.79 and N-NH 3 levels of 4.66, 20.25, 12.56 and 7.81 mg/dL, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The dairy cows studied had adequate mean daily feed intake (18.95 kg DM/cow) and feed intake/BW (3.49 kg DM/100 kg BW). Feed intake was close to the 17.26 kg DM cow/day reported in another study of cows with similar milk production potential and receiving a similar roughage:concentrate ratio (Magalhães et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The animals fed CAS (lower than HCKO), after 24 hours fasting, still had 19.22% of the final body weight in their gastrointestinal tract. This is due to the low rate of passage of this diet, which has low digestibility (Magalhães et al, 2006). Sañudo & Sierra (1986) reported that kill-out is related to production per unit of weight and is variable in sheep (40-60%) because of numerous intrinsic factors (Osório & Osório, 2005) such as genotype, age, sex, type of delivery, degree of fat and weight, as well as extrinsic factors such as number of hours fasting, breeding system, feeding system, stress and cooling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, sugarcane has a high concentration of soluble carbohydrates, an energy source readily available for microbial growth in the rumen. Previous studies have evaluated the substitution of corn silage by sugarcane (MENDONÇA et al, 2004;COSTA et al, 2005;MAGALHÃES et al, 2006;SOUSA et al, the optimum CP content for maximum efficiency of N use without reducing milk yield. Thus, this study aimed to evaluate the effect of using whole raw soybean grain or cottonseed meal associated with two dietary CP content, and their interactions, on the digestive metabolism, lactating performance and efficiency of dietary N utilization in dairy cows fed sugarcane as forage.…”
Section: Introductionmentioning
confidence: 99%